2020
DOI: 10.1158/0008-5472.can-19-0650
|View full text |Cite
|
Sign up to set email alerts
|

Mevalonate Pathway Provides Ubiquinone to Maintain Pyrimidine Synthesis and Survival in p53-Deficient Cancer Cells Exposed to Metabolic Stress

Abstract: Oncogene activation and loss of tumor suppressor function changes the metabolic activity of cancer cells to drive unrestricted proliferation. Moreover, cancer cells adapt their metabolism to sustain growth and survival when access to oxygen and nutrients is restricted, such as in poorly vascularized tumor areas. We show here that p53-deficient colon cancer cells exposed to tumor-like metabolic stress in spheroid culture activated the mevalonate pathway to promote the synthesis of ubiquinone. This was essential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 56 publications
4
43
0
Order By: Relevance
“…Additionally, GGPP is required for the synthesis of ubiquinone and dolichol (Hooff et al, 2010), and depletion of these metabolites may contribute to the proliferation defect observed. In support of this, a recent study demonstrated that inhibition of the mevalonate pathway induced apoptosis in p53-deficient colon cancer cells by decreasing ubiquinone levels, thereby impairing the synthesis of pyrimidine nucleotides (Kaymak et al, 2020). Finally, the incomplete rescue observed in cholesterol-replete media may be because excess cholesterol can induce cytotoxicity by generating ER stress (Fu et al, 2012;Maxfield and Tabas, 2005).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Additionally, GGPP is required for the synthesis of ubiquinone and dolichol (Hooff et al, 2010), and depletion of these metabolites may contribute to the proliferation defect observed. In support of this, a recent study demonstrated that inhibition of the mevalonate pathway induced apoptosis in p53-deficient colon cancer cells by decreasing ubiquinone levels, thereby impairing the synthesis of pyrimidine nucleotides (Kaymak et al, 2020). Finally, the incomplete rescue observed in cholesterol-replete media may be because excess cholesterol can induce cytotoxicity by generating ER stress (Fu et al, 2012;Maxfield and Tabas, 2005).…”
Section: Discussionmentioning
confidence: 89%
“…Negative feedback mechanisms maintain homeostasis in biological systems, and disruption of these regulatory mechanisms can trigger oncogenic transformation or drive malignant progression (Courtois-Cox et al, 2006;Zhao et al, 2015). Despite the stringent negative feedback exerted on the mevalonate pathway by unesterified cholesterol, mevalonate pathway genes are commonly up-regulated in cancer Kaymak et al, 2020;Moon et al, 2019;Turrell et al, 2017). How cancer cells escape cholesterol feedback inhibition to hyperactivate the mevalonate pathway is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, increasing evidence has shown that cancer does not occur in mice with p53 mutations, which nonetheless retain p53 activity for regulation of energy metabolism; this suggests that p53 activities in the context of metabolic regulation may be critical for suppression of tumorigenesis [51]. Numerous cancer studies of the metabolic pathways regulated by p53 have been conducted recently [52][53][54]. As noted by Gomes et al in their review article, p53 activation is involved in the complex process of reprogramming cancer glucose metabolism [55].…”
Section: Discussionmentioning
confidence: 99%